Perception Low Grade Teachers to Thematic Learning on Curriculum 2013 at Sumber Rahayu OKU Timur Elementary School - Astuti, Puji (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
The teacher as a human resource is directly confronted with the presence of students. Therefore teachers must equip themselves with various competencies, starting from the preparation of learning administration that must be fulfilled and made. Therefore, it is reasonable if a teacher plays an important role in learning in school. Therefore, it is natural that the existence of teachers plays a very important role in carrying out learning in schools. The research objective was to describe the perceptions of low-grade teachers in implementing thematic learning in the curriculum 2013 at Sumber Rahayu OKU Timur Elementary school. This research is qualitative research that contains words to describe the object under study by collecting data first at the time of the research by using documentation and interviews conducted from April to June 2020. The results of this study are the perception of low-grade teachers on thematic learning in the curriculum 2013 is that (1) the existence and accuracy of the preparation of RPP strongly support the success of learning, (2) learning can be done with interesting and fun even though the teacher does not fully understand the curriculum 2013, (3) the existence of facilities and infrastructure owned by the school to support teaching activities are still inadequate, (4) the overall assessment in the 2013 curriculum was felt to be a quite difficult and complicated burdensome teacher. Recommended, it is necessary to prepare an appropriate thematic learning design according to the 2013 curriculum before learning in class.Keywords: teacher perceptions, learning thematic, curriculum 2013